Halal enzymatic cosmetic ingredients: The role of enzymes in ingredients selection - Dwicesaria, Maheswari Alfira; Safithri, Mega; Andrianto, Dimas; Purwanto, Ukhradiya Magharaniq Safira (IPB University, 2024)
The rising demand for halal products, especially within the cosmetics industry, has increased the need for cosmetic products to comply with Islamic laws. One of the challenges in achieving halal certification is the determination of the source of the active ingredients used in cosmetic products, such as enzymes. According to Islamic laws, enzymes derived from pigs or other animals that are not slaughtered are not considered halal. To ensure that the enzymes used in cosmetics are derived from halal sources, it is necessary to use enzymes generated from microorganisms through fermentation, provided that the raw materials and growth medium comply with Islamic laws. Additionally, halal cosmetics must meet regional and international standards, including the Indonesian Ulema Council’s Fatwa and the Malaysian Cosmetic and Personal Care Standards. This research provides a comprehensive review of the role of enzymes in selecting halal compliance cosmetic ingredients, focusing on the source of enzymes as a means of assessing the halalness of cosmetic products. It is essential to utilize halal enzymes such as those derived from plants to provide Muslim consumers with assurance when using cosmetic products.